Penerapan Hukum Islam di Indonesia - Sirojudin Ahmad (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to analyze the application of Islamic law in Indonesia in the context of a pluralistic national legal system. As a Muslim-majority country, various aspects of Islamic law have been accommodated in legislation, especially in the fields of family law, Islamic banking, and zakat. This study uses a qualitative method with a literature study approach, examining Islamic legal regulations, fatwas, and their implementation in the Indonesian legal system. The results showed that the implementation of Islamic law in Indonesia is progressing gradually through legal-formal policies, such as the Islamic Law Compilation (KHI) and the Sharia Banking Law. However, challenges remain, especially in the aspect of harmonization with national law and the principle of diversity. This study emphasizes that the implementation of Islamic law in Indonesia must consider contextual aspects in order to remain in harmony with the values of justice and diversity in society.